A novel caged Cookson‐type reagent toward a practical vitamin D derivatization method for mass spectrometric analyses. (19th February 2020) - Seki, Masahiko; Sato, Makoto; Takiwaki, Masaki; Takahashi, Koji; Kikutani, Yoshikuni; Satoh, Mamoru; Nomura, Fumio; Kuroda, Yutaka; Fukuzawa, Seketsu
Abstract : Rationale: 25‐Hydroxylated vitamin D is the best marker for vitamin D (VD). Due to its low ionization efficiency, a Cookson‐type reagent, 1, 2, 4‐triazoline‐3, 5‐dione (TAD), is used to improve the detection/quantification of VD metabolites by liquid chromatography/tandem mass spectrometry (LC/MS/MS). However, the high reactivity of TAD makes its solution stability low and inconvenient for practical use. We here describe the development of a novel caged Cookson‐type reagent, and we assess its performances in the quantitative and differential detection of four VD metabolites in serum using LC/MS/MS. Methods: Caged 4‐(4′‐dimethylaminophenyl)‐1, 2, 4‐triazoline‐3, 5‐dione (DAPTAD) analogues were prepared from 4‐(4′‐dimethylaminophenyl)‐1, 2, 4‐triazolidine‐3, 5‐dione. Their stability and reactivity were examined. The optimized caged DAPTAD (14‐(4‐(dimethylamino)phenyl)‐9‐phenyl‐9, 10‐dihydro‐9, 10‐[1, 2]epitriazoloanthracene‐13, 15‐dione, DAP‐PA) was used for LC/MS/MS analyses of VD metabolites. Results: The solution stability of DAP‐PA in ethyl acetate dramatically improved compared with that of the non‐caged one. We measured the thermal retro‐Diels‐Alder reaction enabling the release of DAPTAD and found that the derivatization reaction was temperature‐dependent. We also determined the detection limit and the lower limit of quantifications for four VD metabolites with DAPTAD derivatization. Conclusions: DAP‐PA was stable enough for mid‐ to long‐term storage in solution. This advantage shall contribute to the detection and quantification of VD in clinical laboratories, and as such to the broader use of clinical mass spectrometry.